High temperature oxidation behaviour of nanocrystalline Fe80Cr20 alloys and ferritic steel implanted with lanthanum and titanium - Saryanto, Hendi (2011)
Fe-Cr alloys and ferritic steel have received considerable attention as Solid Oxide Fuel Cell (SOFC) interconnects material. However, the main problem with the use of Fe-Cr alloys and ferritic steels as interconnect materials is their inadequate high temperature oxidation resistance. Chromium dioxide as the protective layers becomes non protective, due to formation of crack and volatile Cr2O3 upon exposure at high temperature oxidation. The prepared Fe80Cr20 alloy with smallest crystallite size expected to develop a protective film of Cr2O3 scales. On other hand, surface treatment via ion implantation technique can improve the oxidation resistance of alloys. Therefore, the purpose of this study is to investigate the oxidation resistance of implanted and unimplanted Fe80Cr20 alloy and available commercial ferritic steel in normal atmosphere over the temperature range of 1173-1373 K. Nanocrystalline Fe80Cr20 alloys have been produced by mechanical alloying process followed by hot compaction process. Lanthanum and titanium dopant were implanted into substrate of specimens with ion doses of 1x10 17 2 ions/cm . Implanted and unimplanted of specimens were subjected to oxidation at 1173 K, 1273 K, and 1373 K for 100 h. Morphology characterization of oxide scales of specimens were investigated by XRay Diffraction (XRD) and Scanning Electron Microscope (SEM) coupled with